(untitled) (Construction Economics and Building, 2018)
Willie Tan Research Methods: A Practical Guide for Students and Researchers World Scientific Publishing, Singapore, 2017 ISBN: 978-981-3229-58-7 (hardcover), ISBN: 978-981-3229-61-7 (softcover). 228 pages